SISTEM PENGENALAN WAJAH SEBAGAI AKSES LOKER PENYIMPANAN BARANG MENGGUNAKAN ESP32-CAM (STUDI KASUS: PT BUMI NUSANTARA JAYA) - Helmy Agus Pradita; Deanna Durbin Hutagalung (CV. Multi Kreasi Media, 2023)
Face recognition is one of the most studied and developed biometric technologies, in which the device uses a facial recognition algorithm to distinguish individuals based on existing data. Biometric technology is specifically designed to recognize the characteristics of the human biological side, enabling the system to identify, recognize and capture objects on a digital screen. At the PT Bumi Nusantara Jaya company, all employees get their respective lockers and locker keys using a pin and key password that can only be opened by the employee so if someone forgets the locker code and loses the key it is very difficult to open it. The room security system is very good, but the author sees that there are still deficiencies, namely the document storage lockers that are still manually using a code that sometimes forgets the code and the master key is tucked in, even swapped because of the same shape, color and size. Therefore we need a facial recognition system known as a biometric system. In biometric recognition using body parts such as fingers, retina, face, palms. On this occasion the author takes one of the biometrics, namely facial recognition or commonly called face recognition. By using a tool in the form of a camera to recognize faces. To overcome this problem, a Face Recognition System was created to Access Goods Storage Lockers Using ESP32-CAM. In this study using the prototype method, where the flow and stages used include surveys, interviews, literature study, implementation, and testing. The results of this study are in the form of a facial recognition system which is expected to facilitate access to secure locker storage at PT Bumi Nusantara Jaya.